FAKTOR-FAKTOR YANG MEMPENGARUHIPERILAKU BELANJA ONLINE (Studi Kasus Pada Mahasiswa Universitas 17 Agustus 1945 Jakarta) - Donald Picauly (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2015)
The background of this research was the increasing potential market of online shopping inIndonesia but little is known about the behavior of online shopping in Indonesia. Very few studieshad been conducted in Indonesia about online shopping. This research try to fill the gap and giveuseful information for online marketers.The objective of this research was to examine the factors thatinfluence online shopping behavior. The design of this research applies a explanatory andquantitative research design. Survey research using questioner was used to collect the data.Samples was chosen through purposive sampling recruiting a total of 140 samples. Data analysisused in this research was SEM Analysis.The result of this research conclude that the best predictorfor onlineshopping behavior are perceived usefulness, trust, and intention to do online shopping.While perceived ease of use influence perceived usefulness significantly. This result can serve as aguideline for firms in online shopping business to strategize their marketing approaches that causebuying behavior.